Biotechnology in the Courtroom: Applications and Frontiers in Criminal Investigation - Khusbhu Katiyar (AG Volumes, 2026)
Biotechnology is a game-changing technology for contemporary criminal investigations, bringing together molecular biology, genetics, microbiology, and bioinformatics into forensic science and judicial practices. This review addresses the role of biotechnology in the courtroom, its scientific principles, the key techniques in forensic biotechnology, and the significance of biological evidence in criminal investigations. It addresses major applications such as DNA Profiling, Crime scene investigation, Kinship analysis, Forensic toxicology, Disaster victim identification, Sexual assault investigation, Forensic genealogy, etc. that have greatly enhanced the accuracy and reliability of human identification. The review also delves into new areas like next generation sequencing, forensic epigenetics, transcriptomics, proteomics, microbiomics, artificial intelligence and rapid DNA technologies that are transforming forensic practice. Further, it examines the admissibility, ethical issues and regulations relating to biotechnology evidence in India. Finally, the review highlights future developments that will further support evidence-based investigations, improve judicial decision-making and create a more effective, transparent, and technologically advanced criminal justice system.